ANALISIS PENGARUH CAR DAN BOPO TERHADAP ROA DENGAN NIM SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN PERBANKAN SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) DAN OTORITAS JASA KEUANGAN (OJK) PERIODE 2018 – 2022 - Ahmad Sumarlan; Cahyani, Dwi; Hesti Setiorini (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR) and Operating Costs to Operating Income (BOPO) on Return on Assets (ROA) with Net Interest Margin (NIM) as a mediating variable in Islamic banking companies listed on the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK) for the 2018–2022 period. The research method used is a quantitative method with secondary data obtained from the annual financial reports of Islamic banks, with a purposive sampling technique to obtain 11 Islamic banks as research samples. Data analysis was carried out using Partial Least Squares (PLS) with the help of the SmartPLS application. The results of the study indicate that CAR has a positive and significant effect on ROA, BOPO has a negative but not significant effect on ROA, CAR has a positive and significant effect on NIM, BOPO has a negative and significant effect on NIM, and NIM has a positive and significant effect on ROA. In addition, NIM is proven to be able to significantly mediate the effect of CAR and BOPO on ROA. The conclusion of this study is that capital adequacy and operational efficiency of Islamic banks play a significant role in increasing profitability, both directly and indirectly through increased Net Interest Margin. Keywords: CAR, BOPO, NIM, ROA, Islamic Banking